The promise of bitcoin : the future of money and how it can work for you - Lee, Bobby C. (McGraw Hill, 2021)
"From the cofounder of the longest-running bitcoin exchange comes a compelling argument for how this digital currency will transform the global economy-and how it can work for you. Bitcoin may be the best investment opportunity of our time, yet most people have yet to understand its promise. In this book, Bobby Lee, one of the earliest, most successful pioneers in the cryptocurrency space, debunks myths and dispels fears that surround bitcoin, arguing that this rational, logical system is superior to traditional monetary systems. Lee cites signs of bitcoin's widening acceptance: a growing community of users worldwide and multiple initiatives for investing in and holding bitcoin among major financial services organizations and institutional investors who control trillions in assets. Lee offers a primer on the best strategies for purchasing and investing in this digital currency. He discusses the pros and cons, and covers the more complicated method of acquiring bitcoin, mining. He predicts developments in regulation, technology, business, and society that will lead to bitcoin's price increasing 500 percent over the next two decades. In the wake of the current economic crisis, Lee calls on consumers to embrace a technology that will not only increase their wealth but make their lives easier"--